Iron-based nanosheet catalyst for oxidizing organic light filter as well as preparation method and application of iron-based nanosheet catalyst

By using FE3O4 carrier base and NIO/MNO2 composite oxide activity component components, the iron -based nanimonal catalysts are used to solve the problem of removal of organic filtrates such as salicylic acid ethyl ester in the water body, and the efficient and environmentally friendly oxidation degradation is achieved. Effect.

CN119368196APending Publication Date: 2025-01-28NANJING TECH UNIV +2
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411505624.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-28
Publication Date
2025-01-28

AI Technical Summary

Technical Problem

The prior art is difficult to effectively remove organic filters such as ethylhexyl salicylate from water bodies. The traditional treatment method is complex, has high cost and limited removal ability.

Method used

Use Fe3O4 as a carrier -based base, NIO and MNO2 composite oxides as active components, dilute hydrochloric acid and sodium dulate sodium sodium as a morphological control agent, hydrogen peroxide as a surfactant, through secondary water thermal -secondary high temperature roasting Legal iron -prepared nanimum catalyst.

Benefits of technology

The catalyst can efficiently catalyze the oxidation degradation of the alvicolate esters at room temperature. The removal efficiency reaches 100%, the average removal rate is 2ml/min, and the catalyst can still maintain 100%efficiency ten times.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119368196A_ABST
    Figure CN119368196A_ABST
Patent Text Reader

Abstract

The invention discloses an iron-based nanosheet catalyst for oxidizing an organic filter as well as a preparation method and application thereof, and is characterized in that Fe3O4 is taken as a carrier substrate, a NiO and MnO2 composite oxide is taken as an active component, diluted hydrochloric acid and sodium dodecyl sulfate are taken as morphology control agents, hydrogen peroxide is taken as a surface modifier, and a secondary hydrothermal-secondary high-temperature roasting method is adopted to prepare the iron-based nanosheet catalyst. By taking the mass of the carrier substrate as a reference, the mass percentage of the active component is 3-5%. Iron salt, a morphology control agent and deionized water are subjected to hydrothermal treatment and then subjected to high-temperature roasting to prepare a nanosheet carrier substrate, then a mixture of nickel salt and manganese salt is loaded on the surface of the carrier substrate through a hydrothermal method, and finally the iron-based nanosheet catalyst is obtained through high-temperature roasting and surface oxidation modification. The catalyst is environment-friendly and low in cost, can catalytically oxidize the organic filter in sewage at normal temperature, and has important economic benefits and social benefits.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to an iron-based nanosheet catalyst for oxidizing an organic light filter and a preparation method thereof, and belongs to the field of environmentally friendly catalytic materials and water pollution control. Background Art

[0002] Organochlorine photosensitive agents (OUVFs) are one of the important new pollutants. They refer to aromatic organic compounds with heterocyclic or carbonyl conjugation. They are widely used in sunscreens and skin care products because they can absorb ultraviolet UV-A / B. OUVFs can usually enter the water environment through washing of skin during human water recreational activities (such as swimming and seaside bathing), and discharge of domestic sewage without centralized treatment, and persist for a long time, especially in coastal areas with developed marine entertainment industries. The overall level is ng / L-μg / L level, and a few even reach mg / L level. Due to its high octanol-water partition coefficient (logKow=4-8), OUVFs can eventually be ingested by aquatic organisms and accumulate in the body for a long time. Commonly used treatment methods include adsorption, membrane separation, ordinary oxidation, biological methods, etc., but these methods have the disadvantages of complex process flow, high equipment requirements, high cost, and damage to the microenvironment, and the ability of traditional treatment technology to remove such pollutants is very limited. Therefore, it is necessary to study processes with better degradation effects to further improve the water quality of sewage treatment.

[0003] Catalytic oxidation is a method that can completely solve water pollution. It uses hydrogen peroxide to completely oxidize ethylhexyl salicylate, and the catalytic material can be recycled and reused, and will not remain in the wastewater to cause secondary pollution to the environment. However, the existing technology rarely develops corresponding catalysts for organic filters such as ethylhexyl salicylate, so it is of great significance to use catalytic materials to treat dyes such as methyl orange, p-nitrophenol, and methylene blue. Therefore, the development of a highly efficient oxidative degradation effect for organic filters such as ethylhexyl salicylate has important scientific research value and social significance. Summary of the invention

[0004] The purpose of the present invention is to propose a novel catalyst having a highly efficient oxidative degradation effect on organic filters such as ethylhexyl salicylate in view of the current status and existing problems in the field of water pollution treatment. Another purpose of the present invention is to provide a method for preparing the above catalyst.

[0005] The technical scheme of the present invention is: using Fe3O4 as a carrier substrate, NiO and MnO2 composite oxides as active components, dilute hydrochloric acid and sodium dodecyl sulfate as morphology control agents, hydrogen peroxide as a surface modifier, and adopting a secondary hydrothermal-secondary high-temperature roasting method for preparation; based on the mass of the carrier substrate, the mass percentage of the active components is 3% to 5%.

[0006] Preferably, the mass ratio of NiO and MnO2 in the above active components is 1.0:(0.5-1.0).

[0007] The present invention also provides a method for preparing a manganese-nickel-copper based water treatment catalyst, the specific steps of which are:

[0008] (1) Preparation of carrier substrate

[0009] The iron salt, dilute hydrochloric acid, sodium dodecyl sulfate and deionized water are mixed evenly, and then placed in a hydrothermal reactor for high-temperature hydrothermal reaction. After the hydrothermal reaction is completed, the mixture is filtered and dried, and then placed in a muffle furnace for high-temperature calcination to obtain a Fe3O4 carrier substrate.

[0010] (2) Catalyst preparation

[0011] Weigh nickel salt and manganese salt, add deionized water and stir evenly to obtain an active component precursor solution, then place the Fe3O4 carrier substrate obtained in step (1) in the active component precursor solution, mix evenly and place in a hydrothermal reactor for low-temperature hydrothermal reaction, filter and dry after the hydrothermal reaction, then place in a muffle furnace for high-temperature calcination to obtain a catalyst powder, and then place the catalyst powder in hydrogen peroxide for surface modification, thereby obtaining an iron-based nanosheet catalyst.

[0012] Preferably, the iron salt in step (1) is one of ferric nitrate nonahydrate or ferric chloride hexahydrate, and the dilute hydrochloric acid is a hydrochloric acid solution with a mass fraction of 3 to 7%.

[0013] Preferably, the mass ratio of the iron salt, dilute hydrochloric acid, sodium dodecyl sulfate and deionized water in step (1) is 1: (0.2-0.8): (0.1-0.5): (40-60).

[0014] Preferably, the temperature of the high-temperature hydrothermal reaction in step (1) is 160-180°C, the time of the high-temperature hydrothermal reaction is 24-48 hours, the drying temperature is 80-100°C, the drying time is 6-12 hours, the high-temperature calcination temperature is 600-800°C, and the high-temperature calcination time is 2-4 hours.

[0015] Preferably, the nickel salt in step (2) is one of nickel nitrate hexahydrate or nickel chloride hexahydrate, the manganese salt is one of manganese chloride or manganese nitrate hexahydrate, and the mass ratio of the nickel salt to deionized water is 1:(400-600).

[0016] Preferably, the temperature of the low-temperature hydrothermal reaction in step (2) is 100-120°C, the time of the low-temperature hydrothermal reaction is 6-12h, the temperature of the drying is 80-100°C, the time of the drying is 6-12h, the temperature of the high-temperature calcination is 500-700°C, and the time of the high-temperature calcination is 2-4h.

[0017] Preferably, the hydrogen peroxide in step (2) is a hydrogen peroxide solution with a mass fraction of 8 to 16%, and the mass ratio of the catalyst powder to the hydrogen peroxide is 1:(15 to 30).

[0018] The catalytic reaction conditions and results of the present invention are as follows: 1g of catalyst sample is loaded into a catalyst performance evaluation reaction device, and a reaction solution is introduced for activity evaluation. The concentration of the solution is: 50mL of ethylhexyl salicylate ethanol solution (ethanol is a solvent, wherein the mass concentration of ethylhexyl salicylate is 10mg / L), 50mL of hydrogen peroxide (mass fraction is 10%). The catalyst removes ethylhexyl salicylate at room temperature and pressure with an efficiency of 100%, an average removal rate of 2mL / min, and the efficiency of the catalyst can still be maintained at 100% after ten times of use.

[0019] Beneficial effects:

[0020] The catalyst prepared by the present invention can efficiently catalyze and reduce organic filters such as ethylhexyl salicylate. Compared with the prior art, the catalyst system uses Fe3O4 as a carrier substrate, which can not only utilize the magnetism of Fe3O4 to facilitate recycling after use, but also utilize Fe 2+ and Fe 3+ The electron conversion and transmission performance of the active component nickel-manganese composite oxide is improved; dilute hydrochloric acid and sodium dodecyl sulfate are used as morphology control agents to promote the growth of Fe3O4 into nanosheets under high-temperature hydrothermal conditions, increase the contact between the catalyst surface and ethylhexyl salicylate, and thus facilitate the activation of the reaction molecules; NiO in the active component has excellent CC bond breaking performance, and MnO2 has excellent oxidation performance, which can effectively activate hydrogen peroxide in the reaction process into hydroxyl groups and peroxide ions, and use hydroxyl groups and peroxide ions to oxidize ethylhexyl salicylate and promote its oxidative degradation; in addition, during the catalyst preparation process, the oxidative self-decomposition of hydrogen peroxide on the catalyst surface is used, and hydroxyl groups and peroxide ions will promote the increase in the number of hydroxyl groups on the surface of the active component nickel-manganese composite oxide, further improving the catalytic activity. Therefore, the catalyst of the present invention can efficiently catalyze and oxidize organic light filters in sewage at room temperature, and the catalyst component is environmentally friendly, the preparation process is simple, the cost is low, the cost performance is high, and it has a strong application and promotion value. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 This is the SEM image of the catalyst prepared in Example 1;

[0022] Figure 2 This is the SEM image of the catalyst prepared in Comparative Example 1. DETAILED DESCRIPTION

[0023] The present invention is further described below in conjunction with the embodiments, but the protection scope of the present invention is not limited thereto: Embodiment 1

[0024] (1) Preparation of carrier substrate

[0025] Weigh 10.469 g of ferric nitrate nonahydrate, 2.094 g of 3% hydrochloric acid solution, 1.047 g of sodium dodecyl sulfate, and 418.760 g of deionized water, mix them evenly, and then place them in a hydrothermal reactor for a high-temperature hydrothermal reaction at 160° C. for 48 h. After the hydrothermal reaction is completed, filter them, place them in an oven for drying at 80° C. for 12 h, and then place them in a muffle furnace for high-temperature calcination at 600° C. for 4 h to obtain a Fe3O4 carrier substrate;

[0026] (2) Catalyst preparation

[0027] Weigh 0.156g of nickel nitrate hexahydrate and 0.029g of manganese chloride, add 62.400g of deionized water and stir evenly to obtain an active component precursor solution, then place 2g of the Fe3O4 carrier substrate obtained in step (1) in the active component precursor solution, mix evenly and place in a hydrothermal reactor for low-temperature hydrothermal reaction at 100°C for 12h, filter after the hydrothermal reaction, place in an oven for drying at 80°C for 12h, then place in a muffle furnace for high-temperature baking at 500°C for 4h to obtain a catalyst powder, then place 2.06g of the catalyst powder in 30.900g of 8% hydrogen peroxide for surface modification for 2h, thereby obtaining an iron-based nanosheet catalyst; in the catalyst, the mass percentage of the active component is 3% based on the mass of the carrier substrate, and the mass ratio of NiO and MnO2 in the active component is 1:0.5.

[0028] (3) Catalytic activity test

[0029] Take 1g of catalyst sample and put it into the catalyst performance evaluation reaction device, and pass the reaction solution to evaluate the activity. The concentration of the solution is: 50mL ethylhexyl salicylate ethanol solution (ethanol is the solvent, where the mass concentration of ethylhexyl salicylate is 10mg / L), 50mL hydrogen peroxide (mass fraction is 10%). The catalyst removes ethylhexyl salicylate at room temperature and pressure. The efficiency reaches 100%, the average removal rate is 2mL / min, and the efficiency of the catalyst can still maintain 100% after ten times of use.

[0030] Embodiment 2:

[0031] (1) Preparation of carrier substrate

[0032] Weigh 7.005g of ferric chloride hexahydrate, 5.604g of 7% hydrochloric acid solution, 3.503g of sodium dodecyl sulfate, and 420.300g of deionized water, mix them evenly, and then place them in a hydrothermal reactor for high-temperature hydrothermal reaction at 180°C for 24h. After the hydrothermal reaction is completed, filter and place them in an oven for drying at 100°C for 6h, and then place them in a muffle furnace for high-temperature calcination at 800°C for 2h to obtain a Fe3O4 carrier substrate;

[0033] (2) Catalyst preparation

[0034] Weigh 0.159 g of nickel chloride hexahydrate and 0.165 g of manganese nitrate hexahydrate, add 95.4 g of deionized water and stir evenly to obtain an active component precursor solution, then place 2 g of the Fe3O4 carrier substrate obtained in step (1) in the active component precursor solution, mix evenly and place in a hydrothermal reactor for low-temperature hydrothermal reaction at 120° C. for 6 h, filter after the hydrothermal reaction, place in an oven for drying at 100° C. for 6 h, then place in a muffle furnace for high-temperature roasting at 700° C. for 2 h to obtain a catalyst powder, then place 2.10 g of the catalyst powder in 63.000 g of hydrogen peroxide with a mass fraction of 16% for surface modification for 2 h, thereby obtaining an iron-based nanosheet catalyst; in the catalyst, the mass percentage of the active component is 5% based on the mass of the carrier substrate, and the mass ratio of NiO and MnO2 in the active component is 1:1.

[0035] (3) Catalytic activity test

[0036] Take 1g of catalyst sample and put it into the catalyst performance evaluation reaction device, and pass the reaction solution to evaluate the activity. The concentration of the solution is: 50mL ethylhexyl salicylate ethanol solution (ethanol is the solvent, where the mass concentration of ethylhexyl salicylate is 10mg / L), 50mL hydrogen peroxide (mass fraction is 10%). The catalyst removes ethylhexyl salicylate at room temperature and pressure. The efficiency reaches 100%, the average removal rate is 2mL / min, and the efficiency of the catalyst can still maintain 100% after ten times of use.

[0037] Comparative Example 1

[0038] (1) Catalyst preparation

[0039] Except that sodium dodecyl sulfate was not used as a morphology control agent during catalyst preparation, other conditions were the same as those in Example 1;

[0040] (2) Catalytic activity test

[0041] Take 1g of catalyst sample and put it into the catalyst performance evaluation reaction device, and pass the reaction solution to evaluate the activity. The concentration of the solution is: 50mL ethylhexyl salicylate ethanol solution (ethanol is the solvent, where the mass concentration of ethylhexyl salicylate is 10mg / L), 50mL hydrogen peroxide (mass fraction is 10%). The catalyst removes ethylhexyl salicylate at room temperature and pressure. The efficiency reaches 32%, and the average removal rate is 2mL / min.

[0042] (3) Contrast effect

[0043] Compared with Example 1, if sodium dodecyl sulfate is not used as a morphology control agent during catalyst preparation, the catalyst does not form nanosheets, but grows into micron-sized block particles with an uneven surface and a nanoporous structure ( Figure 2 ), the nanocatalytic effect of the catalyst disappears significantly, which is not conducive to the activation of the reaction molecules on the catalyst surface, so the catalytic efficiency is significantly reduced.

[0044] Comparative Example 2:

[0045] (1) Catalyst preparation

[0046] Except that hydrogen peroxide was not used for surface modification during catalyst preparation, other conditions were the same as those in Example 2;

[0047] (2) Catalytic activity test

[0048] Take 1g of catalyst sample and put it into the catalyst performance evaluation reaction device, and pass the reaction solution to evaluate the activity. The concentration of the solution is: 50mL ethylhexyl salicylate ethanol solution (ethanol is the solvent, where the mass concentration of ethylhexyl salicylate is 10mg / L), 50mL hydrogen peroxide (mass fraction is 10%). The catalyst removes ethylhexyl salicylate at room temperature and pressure. The efficiency reaches 68%, and the average removal rate is 2mL / min.

[0049] (3) Contrast effect

[0050] Compared with Example 2, if hydrogen peroxide surface modification is not used during catalyst preparation, the number of hydroxyl groups on the catalyst surface that can participate in activation and reaction will decrease, thereby affecting the reaction rate. Therefore, while the average removal rate remains unchanged, the removal efficiency of ethylhexyl salicylate will decrease.

Claims

1. An iron-based nanosheet catalyst for oxidizing an organic filter, characterized in that: The invention adopts a secondary hydrothermal-secondary high-temperature roasting method to prepare the product with Fe3O4 as carrier substrate, NiO and MnO2 composite oxides as active components, dilute hydrochloric acid and sodium dodecyl sulfate as morphology control agents, and hydrogen peroxide as surface modifier. The mass percentage of the active components is 1% to 15% based on the mass of the carrier substrate.

2. The catalyst according to claim 1, characterized in that: Based on the mass of the carrier substrate, the mass percentage of the active component is 3% to 5%; the mass ratio of NiO to MnO2 in the active component is 1.0:(0.1 to 5); Preferably, the mass ratio of NiO and MnO2 in the active component is 1.0:(0.5-1.0).

3. A method for preparing the catalyst according to claim 1, characterized in that: The preparation method of the catalyst is as follows: (1) Preparation of carrier substrate The iron salt, dilute hydrochloric acid, sodium dodecyl sulfate and deionized water are mixed evenly, and then placed in a hydrothermal reactor for hydrothermal reaction. After the hydrothermal reaction is completed, the mixture is filtered and dried, and then placed in a muffle furnace for calcination to obtain a Fe3O4 carrier substrate. (2) Catalyst preparation Weigh nickel salt and manganese salt, add deionized water and stir evenly to obtain an active component precursor solution, then place the Fe3O4 carrier substrate obtained in step (1) in the active component precursor solution, mix evenly and place in a hydrothermal reactor for hydrothermal reaction, filter and dry after the hydrothermal reaction, then place in a muffle furnace for calcination to obtain catalyst powder, and then place the catalyst powder in hydrogen peroxide for surface modification, thereby obtaining an iron-based nanosheet catalyst.

4. The preparation method according to claim 3, characterized in that: The iron salt described in step (1) is one of ferric nitrate nonahydrate or ferric chloride hexahydrate, and the dilute hydrochloric acid is a hydrochloric acid solution with a mass fraction of 3-7%; The mass ratio of the iron salt, dilute hydrochloric acid, sodium dodecyl sulfate and deionized water is 1: (0.2-0.8): (0.1-0.5): (40-60).

5. The preparation method according to claim 3, characterized in that: The temperature of the hydrothermal reaction in step (1) is 160-180° C., and the time of the hydrothermal reaction is 24-48 hours; the temperature of the drying is 80-100° C., and the time of the drying is 6-12 hours; the temperature of the roasting is 600-800° C., and the time of the roasting is 2-4 hours.

6. The preparation method according to claim 3, characterized in that: The nickel salt in step (2) is one of nickel nitrate hexahydrate or nickel chloride hexahydrate, and the manganese salt is one of manganese chloride or manganese nitrate hexahydrate.

7. The preparation method according to claim 3, characterized in that: The temperature of the hydrothermal reaction in step (2) is 100-120° C., and the time of the hydrothermal reaction is 6-12 hours; the temperature of the drying is 80-100° C., and the time of the drying is 6-12 hours; the temperature of the roasting is 500-700° C., and the time of the roasting is 2-4 hours.

8. The preparation method according to claim 3, characterized in that: The hydrogen peroxide in step (2) is a hydrogen peroxide solution with a mass fraction of 8 to 16%, and the mass ratio of the catalyst powder to the hydrogen peroxide is 1:(15 to 30).

9. Use of the catalyst according to claim 1 in catalytic oxidation of organic filters.

10. The use according to claim 9, characterized in that: The organic filter is ethylhexyl salicylate.